The development of 3D US system for treating target localization in focused ultrasound surgery - Gao, Shuang; Chen, Ya-zhu; Ni, Yang-hua (Zhongguo yi liao qi xie za zhi, 2002)
Focused Ultrasound Surgery (FUS) is a promising minimally invasive technique in tissue ablation. Because of the high intensity at the ultrasound focus, a precise 3D-localization system is required to determine the site of the treating target in order to increase the efficiency and security of FUS. This paper represents a three dimensional ultrasound (3D US) localization system developed and its workflow. The system is mainly composed of imaging and image processing system, movement device and its controlling circuits, and position feedback device. The system has a maximum scan range of +/- 30 degrees with a resolution of 8 levels from 0.54' to 0.36 degrees. For a spherical shape like target, in theory, the maximum diameter is 160 mm the system can treat. The system can be used to localize precisely the treatment targets with general sizes in the suitable parts of the body in FUS.